Mandatory integration agreements for unemployed job seekers: a randomized controlled field experiment in Germany - Gerard J. van den Berg; Barbara Hofmann; Gesine Stephan; Arne Uhlendorff (International Economic Review, 2024)
Integration agreements (IAs) are contracts between the employment agency and the unemployed, nudging the latter to comply with rules on search behavior. We designed and implemented a randomized controlled trial involving thousands of newly unemployed workers, randomizing at the individual level both the timing of the IA and whether it is announced in advance. Administrative records provide outcomes. Novel theoretical and methodological insights provide tools to detect anticipation and suggest estimation by individual baseline employability. The positive effect on entering employment is driven by individuals with adverse prospects. For them, early IA increase reemployment within a year from 53% to 61%.
Keywords: 330